Etika Public Speaking Antarbudaya - Sihabuddin, Sihabuddin; Itasari, Andri Astuti (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research discusses intercultural public speaking ethics, which is a combination of public speaking ethics and intercultural communication ethics. The method used in this research is the library research method, in which researchers conduct research only on library collection materials related to intercultural public speaking ethics. The research results show that a public speaker is not only required to understand public speaking ethics but is also required to understand intercultural communication ethics so that public speakers can apply intercultural public speaking ethics. By applying intercultural public speaking ethics, public speaking with audiences of people from different cultural backgrounds can be effective. To apply intercultural public speaking ethics, public speakers must first learn the culture of their audience by first seeking information regarding what ethics are deemed permissible and not permissible. After studying the cultural ethics of the audience, the public speaker must enter that culture as if the public speaker is part of the members of that culture without leaving the public speaker's own cultural identity.